Tourism in the new Europe : the challenges and opportunities of EU enlargement (CABI, 2006)
This book addresses European tourism within the framework of an enlarged European Union of 25 members. It looks at the substantial reorientation of the organizational framework of European tourism and its profound implications for future structural and geographical patterns of development. Providing a series of thematic evaluations of relationships between tourism and EU enlargement, this book includes a country-by-country examination of each of the new member states, in terms of their current patterns and trends of tourism development and the impacts that EU accession brings to them. The second, third and fourth parts of the book examine, respectively, those new EU entrants from East Central Europe, the Baltics, and the Mediterranean. The fifth part addresses those countries of Southeastern Europe seeking EU accession in the projected 2007 enlargement (or beyond). This book is designed primarily as a textbook for courses and modules on European tourism, but will also be of interest to those working in the areas of tourism, European studies, development studies, geography, sociology and economics. The book has 23 chapters and a subject index.